Khemotaksis Rhizobakteri Osmotoleran pada Rizosfer Tanaman Kacang Hijau (Vigna radiata, L.) - Yekti Maryani (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
This research has an objective to study chemotaxis of osmotolerant rhizobacteria strains Al-19 dan M7b in greenpea plant. These isolates were used to inoculate greenpea plant. The study on chemotaxis of osmotolerant rhizobacteria was conducted by CFU method in order to count the number of osmotolerant rhizobacteria AL-19 dan M7b in rhizosphere. Visualization of those isolates on root surface used fluorescence microscope and agglutination reaction with exudates of greenpea root. Result of the study showed that both isolates of osmotolerant rhizobacteria Al-19 dan M7b were found in rhizosphere of greenpea with low-density. Simple carbohydrate is substrat that is essential for rhizobacteria to grow thus the chemotaxis of both rhizobacteria is considered as metabolism - dependent. It means that it is not only as digested material but also function as affinity substance. These isolates gathered on the root surface weakly and did not make glutination reaction. This condition indicated that these isolates could not form colony on root surface of greenpea.